1997
DOI: 10.1080/0156655970440406
|View full text |Cite
|
Sign up to set email alerts
|

Culturally Responsive Early Intervention Programs: issues in India

Abstract: The influence of economic factors on socio-cultural aspects in traditional, industrial, and "transitional" societies is explored through an examination of the socioeconomic structure and organisation in these societies. Transitional societies are defined as those that are moving from a traditional nature to an industrial one. India is used as an example of a transitional society. Links between the socio-economic contexts of the three societies, their child rearing goals and practices, and features of early int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Early Intervention pertains to the child as well as to the parents, the family and the broader network.' (Heinen, 1997, p.6) The need for culturally sensitive early intervention, as a universal concept, is highlighted by the work of Srinivasan and Karlan (1997) who remind us that the:…”
Section: Early Intervention?mentioning
confidence: 94%
“…Early Intervention pertains to the child as well as to the parents, the family and the broader network.' (Heinen, 1997, p.6) The need for culturally sensitive early intervention, as a universal concept, is highlighted by the work of Srinivasan and Karlan (1997) who remind us that the:…”
Section: Early Intervention?mentioning
confidence: 94%
“…Although close family bonds do not necessarily imply the absence of personal independence (Srinivasan and Karlan 1997), a number of investigators have found such a link within the Indian cultures. Rao et al (2003) used a survey study to investigate group and individual differences between Indian and Chinese mothers of preschoolers regarding parents' socialization goals (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…While the international community has been open to the idea of inclusion, concern has been expressed by scholars about the rush towards transferring special educational practices, such as 'inclusion' from their countries of origin to developing countries (Kalyanpur, 1996;Miles, 1997;Srinivasan & Karlan, 1997). Two arguments consistently recur in the literature.…”
Section: Introductionmentioning
confidence: 96%